Organic primary battery

Through the proton-induced reduction reaction of nitro to amino groups, the problem of limited electron transfer of existing primary battery materials is solved, and the high specific capacity and energy density is improved, which is suitable for a wide range of temperatures and environmental conditions.

CN114142053BActive Publication Date: 2025-04-18TIANJIN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111326372.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-10
Publication Date
2025-04-18
Estimated Expiration
2041-11-10

AI Technical Summary

Technical Problem

The existing primary battery materials have limited electron transfer during discharge, which limits the performance of their specific capacity and energy density.

Method used

Through proton induction, the reduction conversion of nitro compounds to amino compounds is transferred 6 electrons during the reaction process, which increases the specific capacity and energy density of aromatic nitro compounds.

Benefits of technology

The specific capacity reaches more than 1300mAh/g, the energy density reaches more than 3000Wh/kg, and maintain good performance within a wide temperature range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114142053B_ABST
    Figure CN114142053B_ABST
Patent Text Reader

Abstract

The present invention provides an organic primary battery following an amination route, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode uses an aromatic nitro compound as a positive electrode active substance, the aromatic nitro compound is an aromatic nitro compound containing a single benzene ring or multiple benzene rings, the negative electrode is an alkali metal, the electrolyte is an alkali metal salt solution, and the alkali metal salt solution uses a solvent that can provide protons. The present invention reduces and transforms the nitro compound into an amino compound through proton induction, and the reaction process transfers 6 electrons, which greatly improves the specific capacity and energy density of the aromatic nitro compound, and the specific capacity can reach more than 1300mAh / g, and the specific energy can reach more than 3000Wh / kg, which has great application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to an organic primary battery. Background Art

[0002] With the continuous development of social economy, the demand for high specific energy storage systems is increasing. Primary batteries have the advantages of high energy density, small size, and stable performance, and have been widely used in aerospace, military, medical, transportation, and people's livelihood. The primary battery systems that have been commercially applied include lithium-carbon fluoride (Li-CF x ) batteries, lithium-manganese dioxide (Li-MnO2) batteries, lithium-sulfur dioxide (Li-SO2) batteries and lithium-thionyl chloride (Li-SOCl2) batteries, etc.

[0003] For Li-CF x Batteries require the use of highly toxic fluorine gas (F2) to fluorinate carbon materials at high temperatures during the preparation of electrode materials. The preparation process is dangerous and cumbersome, and has high energy consumption, causing serious pollution to the environment. The early mining and processing of MnO2 electrode materials consumes a lot of energy and can also cause serious environmental pollution. Li-SO2 and Li-SOCl2 gas or liquid batteries are prone to leakage of active substances during use, and are prone to safety issues such as thermal runaway.

[0004] Compared with the above materials, aromatic nitro compound electrode materials have the advantages of easy availability of raw materials, low cost, and environmental friendliness, and have the prospect of preparing high specific energy primary battery electrode materials. However, the nitro compound electrode materials reported so far follow the transformation of nitro to -N-OLi structure during discharge, and the reaction process transfers two electrons, which limits its specific capacity and energy density. Therefore, it is necessary to develop new multi-electron reduction reaction mechanisms to improve the specific capacity and energy density of aromatic nitro compounds. Summary of the invention

[0005] The purpose of the present invention is to provide an organic primary battery following the amination route, namely: through proton induction, the reduction conversion of nitro compounds to amino compounds, the reaction process transfers 6 electrons, which greatly improves the specific capacity and energy density of aromatic nitro compounds.

[0006] In order to achieve the above-mentioned purpose, the present invention adopts the following technical scheme: an organic primary battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode uses an aromatic nitro compound as a positive electrode active substance, and the aromatic nitro compound is an aromatic nitro compound containing a single benzene ring or multiple benzene rings, the negative electrode is an alkali metal, and the electrolyte is an alkali metal salt solution, and the alkali metal salt solution uses a solvent that can provide protons.

[0007] Furthermore, the solvent capable of providing protons is: chain ethers, cyclic ethers, chain carbonates, cyclic carbonates, chain esters or cyclic esters.

[0008] Furthermore, the positive electrode is prepared in the following manner: the aromatic nitro compound is uniformly mixed with the conductive agent and the binder to form a uniform slurry, which is then scraped onto the current collector carbon-coated aluminum foil and air-dried.

[0009] Furthermore, the mass content of the aromatic nitro compound is above 30%.

[0010] Furthermore, the electrolyte is a solution of alkali metal salt with a concentration of 0.5-5 mol / L.

[0011] Furthermore, the alkali metal salt is lithium perchlorate LiClO4, sodium perchlorate NaClO4, potassium fluorosulfonyl imide KFSI.

[0012] Furthermore, the battery is operated under acidic gas conditions; and the positive electrode active material is loaded on a carbon paper current collector.

[0013] Compared with the prior art, the invention has the following beneficial effects: the organic primary battery obtained according to the invention has a specific capacity of more than 1300mAh / g and a specific energy of more than 3000Wh / kg, which exceeds the energy density of all organic electrode materials and most high-specific-energy inorganic electrode materials reported so far, and has no obvious self-discharge phenomenon during 3-month storage, can be used in a temperature range of -20°C to 60°C, can be used in a carbon dioxide atmosphere, and meets the use requirements of primary batteries. Moreover, the raw material cost is low, and the application prospect is very promising. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is the specific capacity-voltage discharge curve of the lithium-organic primary battery in Example 1, in which 5-dinitronaphthalene is used as the positive electrode active material, and the electrolyte is 0.5M LiClO4 DME (ethylene glycol dimethyl ether) + 10% FEC (fluoroethylene carbonate, volume fraction).

[0015] Figure 2 This is the specific energy-voltage discharge curve of the lithium-organic primary battery in Example 1, using 5-dinitronaphthalene as the positive electrode active material, and the electrolyte is 0.5M LiClO4 DME+10% FEC (volume fraction).

[0016] Figure 3 This is the self-discharge curve of the lithium-organic primary battery using 5-dinitronaphthalene as the positive electrode active material in Example 1. Intermittent discharge is performed by discharging first and then standing. The standing time for each time is 7 days. The electrolyte is 0.5M LiClO4DME+10% FEC (volume fraction).

[0017] Figure 4 This is the high and low temperature performance curve of the lithium-organic primary battery with 5-dinitronaphthalene as the positive electrode active material in Example 1, the test range is -20°C to 60°C, the current density is 20mA / g, and the electrolyte is 0.5M LiClO4 DME+10% FEC (volume fraction).

[0018] Figure 5 This is the F1s high-resolution spectrum obtained by XPS characterization of the positive electrode sheet of the lithium-organic primary battery of Example 1, where 5-dinitronaphthalene is used as the positive electrode active material and discharged to 2.0V. The electrolyte is 0.5M LiClO4 DME+10% FEC (volume fraction)

[0019] Figure 6 This is the diffraction spectrum obtained by XRD characterization of the positive electrode sheet of Example 1, in which the lithium-organic primary battery with 5-dinitronaphthalene as the positive electrode active material was discharged to 2.0V, and the electrolyte was 0.5M LiClO4 DME+10% FEC (volume fraction).

[0020] Figure 7 This is the spectrum obtained by XPS characterization of the positive electrode sheet of the lithium-organic primary battery in Example 1, where 5-dinitronaphthalene is used as the positive electrode active material and discharged to 2.0V, and the electrolyte is 0.5M LiClO4 DME+10% FEC (volume fraction). Figure 7 (a) is the XPS high-resolution C1s spectrum. Figure 7 (b) is the XPS high-resolution O1s spectrum.

[0021] Figure 8 For Example 1, 5-dinitronaphthalene as the positive electrode active material of the lithium-organic primary battery is discharged to 500mAh / g ( Figure 8 a) and discharge to 2.0V( Figure 8 b) The spectrum obtained by GC-MS characterization of the positive electrode sheet, the electrolyte is 0.5MLiClO4DME+10%FEC (volume fraction).

[0022] Fig. 9 This is the electrochemical reaction mechanism of Example 1, a lithium-organic primary battery with 5-dinitronaphthalene as the positive electrode active material in a 0.5M LiClO4DME+10% FEC (volume fraction) electrolyte.

[0023] Fig.10 The constant current (20 mA / g) discharge curve of the lithium-organic primary battery with 5-dinitronaphthalene as the positive electrode active material in 0.5M LiClO4 DME electrolyte ( Fig.10 a) and infrared spectroscopy ( Fig.10 b)

[0024] Fig.11 These are constant current discharge curves of lithium-organic primary batteries of aromatic nitro compounds of different structures in the examples, with a current density of 20 mA / g and an electrolyte of 0.5 M LiClO4 DME+10% FEC (volume fraction).

[0025] Fig.12 Example 1,5-dinitronaphthalene as the positive electrode active material of the sodium-organic primary battery ( Fig.12 a) and potassium-organic primary batteries ( Fig.12 b) constant current (20mA / g) discharge curve. Fig.12 aThe electrolyte used is 0.5M NaClO4DME+10%FEC (volume fraction), Fig.12 b The electrolyte used is 0.5M KFSI DME + 10% FEC (volume fraction).

[0026] Fig.13 This is the constant current discharge curve of Example 1, where 5-dinitronaphthalene is used as the positive electrode active material and different electrolytes are used, and the current density is 20 mA / g.

[0027] Fig.14 This is the GC-MS spectrum of Example 1, a lithium-organic primary battery using 5-dinitronaphthalene as a positive electrode active material, discharged to 2V in a 0.5MLiClO4DME+10%VC (volume fraction) electrolyte.

[0028] Fig.15 This is the XPS N 1s spectrum of a lithium-organic primary battery with 1,5-dinitronaphthalene as the positive electrode active material in 0.5M LiClO4 DME+10% VC (volume fraction) electrolyte.

[0029] Fig.16 This is the XPS C 1s spectrum of the lithium-organic primary battery with 1,5-dinitronaphthalene as the positive electrode active material in 0.5M LiClO4 DME+10% VC (volume fraction) electrolyte ( Fig.16 a) and O1s( Fig.16 b) Spectrum.

[0030] Fig.17 This is the constant current discharge curve of the lithium-organic primary battery in Example 1, where 5-dinitronaphthalene is used as the positive electrode active material, in a carbon dioxide atmosphere, with a current density of 20 mA / g and an electrolyte of 0.5 M LiClO4 TEGDME.

[0031] Fig.18This is the XPS N 1s spectrum of the lithium-organic primary battery with 5-dinitronaphthalene as the positive electrode active material under a carbon dioxide atmosphere ( Fig.18 a) and C1s spectra ( Fig.18 b). DETAILED DESCRIPTION

[0032] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.

[0033] In the following examples, the high specific capacity and irreversible reaction characteristics of the primary battery are measured by its constant current discharge curve.

[0034] Positive electrodes suitable for the present invention include conventional current collector positive electrodes, self-supporting positive electrodes, and porous current collector positive electrodes that facilitate acid gas penetration, but are not limited thereto. The preparation methods of the above three positive electrodes are as follows:

[0035] The conventional current collector positive electrode, taking the carbon-coated aluminum foil current collector as an example, is prepared as follows: the active material, conductive agent and binder are fully ground into a uniformly mixed slurry in a mortar in a certain proportion, and then coated on the carbon-coated aluminum foil current collector. After natural air drying, it is cut into circular electrode pieces with a diameter of 9 mm, placed in a vacuum oven at 50°C for 8 hours, taken out, and quickly placed in a glove box for use.

[0036] Preparation of self-supporting positive electrode: Add active material, conductive agent and polytetrafluoroethylene emulsion in a certain proportion to a bottle, add a small amount of isopropanol, stir and dry in an oven at 50°C. After taking it out, add several drops of isopropanol to the mixture and stir slowly with a spoon until the system is gel-like. The obtained gel-like substance is rolled into a film using a roller press, and then vacuum dried at 50°C for 8 hours, taken out, and quickly placed in a glove box for use.

[0037] The porous current collector positive electrode, taking the carbon paper current collector positive electrode as an example, is prepared as follows: the positive electrode tested in a carbon dioxide atmosphere uses carbon paper as the current collector. After the active material, the conductive agent and the binder are evenly mixed by ball milling in a ratio of 8:1:1, the mixture slurry is drop-coated on the carbon paper current collector, and then it is taken out after being vacuumed in a vacuum oven at 50°C for 8 hours and quickly placed in a glove box for use.

[0038] Regardless of the form of the positive electrode, its preparation method (including the ratio of active material, conductive agent and binder and specific operation steps) is a common technical means in the field, and those skilled in the art can adjust it according to actual conditions. For the present invention, it is only necessary to ensure that the content of the active material is above 30%.

[0039] Specifically, in the following embodiments, the positive electrode formula is as follows:

[0040] Table 1

[0041]

[0042]

[0043] The electrolyte suitable for the present invention is an electrolyte that can provide protons, at least including a way to generate protons by ionization, and can also include injecting acidic gas (such as carbon dioxide) to obtain protons, so as to further increase the proton concentration and induce amination reaction. The output of protons comes from the solvent of the electrolyte. Therefore, it is only necessary to select a solvent that can generate protons in an ionized state, which can be used in the present invention, including but not limited to chain ethers, cyclic ethers, chain carbonates, cyclic carbonates, chain esters or cyclic esters.

[0044] The preparation of the electrolyte is common knowledge in the art: add alkali metal salt and solvent into a vial in sequence, stir until completely dissolved and set aside.

[0045] Specifically, in the following embodiments, the electrolyte formula is as follows:

[0046] Table 2

[0047]

[0048] The assembly of the battery is also common knowledge in the art: specifically, assemble the CR2032 button battery in an argon glove box in the order of negative electrode shell, stainless steel sheet, positive electrode sheet, polypropylene diaphragm, alkali metal, stainless steel gasket, spring sheet, and positive electrode shell.

[0049] Specifically, in the following embodiments, each component is as follows:

[0050] Table 3

[0051] negative electrode Diaphragm Example 1 lithium PP Example 2 lithium PP Example 3 Sodium, potassium PP Example 4 lithium PP Example 5 lithium Whatman GF / C

[0052] Example 1

[0053] The electrode sheet prepared with 1,5-dinitronaphthalene self-supporting electrode as the active material has an average active material loading of 0.67 mg cm -2 The CR2032 button cell, with metallic lithium as the negative electrode and 0.5M LiClO4DME+10% FEC (volume fraction) as the electrolyte, was assembled and subjected to a constant current discharge test on a Neware battery test system with a current density of 20 mA / g.

[0054] The discharge curve is as follows Figure 1 , 2. When 1,5-dinitronaphthalene is fully discharged to 2.0V, its specific capacity is 1338mAh / g and its energy density is as high as 3273Wh / kg.

[0055] The self-discharge performance of the battery is as follows Figure 3 As shown, after standing for 7 days for every 100 mAh / g specific capacity discharged to a cut-off voltage of 2.0 V, the specific capacity is 1227 mAh / g, and the capacity retention rate is as high as 92%, which shows that the battery has good self-discharge performance.

[0056] Figure 4 The figure shows the constant current discharge curve of the battery at high and low temperatures. The test temperatures are -20℃, 0℃, 25℃ and 60℃ respectively. The test is completed in a constant temperature and humidity test chamber using the Xinwei battery test system. Before starting the test, the battery is left at the specified temperature for 2 hours before the constant current discharge test.

[0057] The electrode sheet discharged to 2.0V at 25℃ was characterized by XPS high-resolution F1s, and the characteristic peak of LiF appeared at the binding energy of 685.6eV ( Figure 5 ). At the same time, XRD characterization was performed on the electrode sheet of 1,5-dinitronaphthalene self-supporting electrode discharged to 2.0V, and it was found that the diffraction peaks of LiF appeared at diffraction angles of 38.7°, 45.0° and 65.5° ( Figure 6 ). This indicates that FEC participated in the reaction during the discharge process and generated LiF. XPS characterization analysis was performed on the electrode sheet discharged to 2.0V ( Figure 7 ), it was found that characteristic peaks belonging to lithium carbonate (Li2CO3), lithium oxalate (Li2C2O4) and polymer lithium salt (ROCOOLi) appeared in the XPS high-resolution C1s and O1s spectra, indicating that FEC participated in the reaction to generate Li2CO3, Li2C2O4 and ROCOOLi.

[0058] The 1,5-dinitronaphthalene electrode sheets discharged to 500 mAh / g and fully discharged to 2 V were characterized by GC-MS analysis, and the molecular weight of 188.1 belonging to 5-nitro-1-aminonaphthalene ( Figure 8 a) and the peak belonging to 1,5-diaminonaphthalene with a molecular weight of 158.1 ( Figure 8 b), indicating that during the discharge process, the nitro compounds are reduced to amino compounds.

[0059] Based on the above analysis, it is inferred that the reaction process of 1,5-dinitronaphthalene electrode in 0.5M LiClO4 DME+10% FEC (volume fraction) electrolyte is as follows: Fig. 9 As shown. That is, FEC undergoes an elimination reaction, removing a molecule of hydrogen fluoride (HF) to generate vinylene carbonate (VC). HF further dissociates to generate free protons (H + ) and F - The former participates in the reduction reaction of the nitro group, and the latter reacts with Li +The reaction generates LiF. The generated VC molecules are further reduced and react with Li + The reaction generates lithium enolate radicals and CO2. The former triggers the free radical polymerization of VC in the system to generate polymer lithium salt ROCOOLi. A part of the latter is directly electrochemically reduced to Li2C2O4, and the other part reacts with H2O in the electrolyte to generate H2CO3, which further ionizes free protons (H + ) and CO3 2- The former participates in the reduction reaction of the nitro group, and the latter reacts with Li + A reaction occurs to generate Li2CO3. 1,5-DNN is electrochemically reduced and reacts with the protons generated by HF and H2CO3 ionization to generate 5-nitro-1-aminonaphthalene and 1,5-diaminonaphthalene in sequence.

[0060] In contrast, using + ) was used to test the electrochemical performance of the electrolyte 0.5M LiClO4+DME. The positive electrode was 1,5-dinitronaphthalene and the negative electrode was metallic lithium. The constant current discharge curve is shown in Fig.10 As shown in a, when fully discharged to 2V, the specific capacity is only 406mAh / g, which is much lower than the specific capacity of the electrolyte that can provide protons. The electrode sheets with different discharge depths were analyzed by infrared spectroscopy ( Fig.10 b) It is found that with the increase of discharge depth, the -1 The characteristic peak intensity of the nitro group gradually weakened, and 1382 cm -1 The characteristic peaks of -N-OLi are shown in Figure 2, which proves that the conversion of nitro group to -N-OLi occurs in this electrolyte.

[0061] In summary, the conversion of nitro groups to amino groups occurs in the electrolyte that can provide protons, which greatly improves its specific capacity.

[0062] Example 2

[0063] Electrode sheets of different aromatic nitro compounds were prepared, with an average active material loading of 0.67 mg cm -2 , refer to Table 1 to Table 3. The negative electrode is metallic lithium, and the electrolyte is 0.5M LiClO4 DME + 10% FEC (volume fraction). The CR2032 button battery assembled was tested on the Neware battery test system with a constant current discharge density of 20mA / g. The electrolyte is 0.5M LiClO4 DME + 10% FEC (volume fraction). They all have the characteristics of primary batteries, and the discharge specific capacity is greater than 950mAh / g. ( Fig.11 )

[0064] Example 3

[0065] Use different alkali metal negative electrodes and 1,5-dinitroanthraquinone as the positive electrode, refer to Table 1 to Table 3. Among them, Fig.12 In a, a metallic sodium negative electrode is used, and the electrolyte is 0.5M NaClO4 DME+10% FEC (volume fraction); Fig.12 In b, a metallic potassium negative electrode is used, and the electrolyte is 0.5M KFSIDME+10% FEC (volume fraction). The assembled CR2032 button cell is subjected to a constant current discharge test on a Neware battery test system, with a current density of 20mA / g. They all have the characteristics of a primary battery, and the discharge specific capacity is greater than 850mAh / g.

[0066] Example 4

[0067] Different electrolytes were configured, 1,5-dinitronaphthalene was used to prepare the electrode material, metallic lithium was used as the negative electrode, and CR2032 batteries were assembled according to the above method to explore the effect of different electrolytes on battery performance. The constant current discharge curve is shown in Fig.13 As shown. The test voltage range is 2.0-3.0V, and the current density is 20mA / g. The electrolytes used are 0.5M LiClO4 DME+10%VC (vinylene carbonate, volume fraction), 0.5M LiClO4 DME+10%EC (ethylene carbonate, volume fraction), 0.5MLiClO4 DME+10%PC (propylene carbonate, volume fraction), 0.5M LiClO4 DEGDME (diethylene glycol dimethyl ether) +10%FEC (volume fraction), 0.5M LiClO4 DEGDME+10%VC (volume fraction) and 0.5M LiClO4 DEGDME+10%EC (volume fraction). Using different electrolytes, the specific capacity is higher than 800mAh / g.

[0068] Fig.14 The GC-MS spectrum of 1,5-dinitronaphthalene electrode fully discharged to 2V in 0.5M LiClO4 DME+10% VC electrolyte is shown, and a peak belonging to 5-nitro-1-aminonaphthalene with a molecular weight of 188.1 appears, proving that the nitro group has been converted to the amino group.

[0069] Fig.15 Shown are unreacted and fully discharged 1,5-dinitronaphthalene electrodes to 2 V. It was found that when fully discharged to 2 V, a characteristic peak belonging to the amino group appeared, which also proved that the conversion of nitro groups to amino groups occurred in the electrolyte.

[0070] Fig.16a and b show the XPS C 1s and O1s spectra of the 1,5-dinitronaphthalene electrode sheet discharged to 2V, with peaks belonging to lithium carbonate, lithium oxalate and ROCOOLi. Based on the above results, the reaction process of the 1,5-DNN electrode in the electrolyte is as follows: VC is electrochemically reduced to lithium enolate radicals and CO2, the former triggers VC polymerization to generate ROCOOLi, part of the latter is reduced to Li2C2O4, and the other part reacts with the electrolyte to generate carbonic acid, the dissociated proton participates in the conversion of nitro group to amino group, and the dissociated carbonate ion reacts with Li in the electrolyte. + The reaction generates Li2CO3. Similarly, the reaction process of 1,5-dinitronaphthalene in 0.5M LiClO4 DME+10%EC and 0.5M LiClO4 DME+10%PC electrolytes is similar to that in 0.5MLiClO4 DME+10%VC, that is, CO2 is generated through electrochemical reduction of EC or PC, and reacts with the electrolyte to generate carbonic acid. The dissociated proton can participate in the conversion of nitro groups to amino groups, making it have a higher specific capacity.

[0071] Example 5

[0072] The battery was assembled using the carbon paper current collector electrode sheet of 1,5-dinitronaphthalene and placed in a CO2 atmosphere for constant current discharge test. Fig.17 When discharged to 2V, the specific capacity is 950mAh / g. Fig.18 a shows the XPS N1s spectrum of the 1,5-dinitronaphthalene electrode discharged to 2 V, in which characteristic peaks belonging to the amino group appear, proving that the nitro group has been converted to the amino group.

[0073] Fig.18 b shows the XPS C 1s spectrum of the 1,5-dinitronaphthalene electrode discharged to 2V, showing characteristic peaks belonging to Li2CO3 and Li2C2O4. Based on the above experimental data, it can be inferred that CO2 can react with the electrolyte to generate carbonic acid, and the protons generated by its ionization can participate in the reduction process of nitro groups to amino groups, and the carbonate ions generated by ionization can react with Li in the electrolyte. + The reaction produces Li2CO3, and CO2 can also be directly reduced to produce Li2C2O4.

[0074] According to Examples 1-5, the aromatic nitro compound electrode material can exhibit the characteristics of a high specific capacity primary battery in the presence of an electrolyte that can provide protons, and a high specific capacity primary battery can be prepared in a CO2 atmosphere.

[0075] The above contents are only preferred embodiments of the present invention. For ordinary technicians in this field, according to the concept of the present invention, there will be changes in the specific implementation methods and application scopes. The content of this specification should not be understood as limiting the present invention.

Claims

1. An organic primary battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte. The positive electrode uses an aromatic nitro compound as a positive electrode active substance, and the aromatic nitro compound is an aromatic nitro compound containing multiple benzene rings. The negative electrode is an alkali metal, and the electrolyte is an alkali metal salt solution. The alkali metal salt solution uses a solvent that can provide protons. The solvent that can provide protons is: cyclic carbonate or fluoroethylene carbonate.

2. The organic primary battery according to claim 1, characterized in that: The positive electrode is prepared in the following manner: the aromatic nitro compound is uniformly mixed with the conductive agent and the binder to form a uniform slurry, which is then scraped and coated on the current collector carbon-coated aluminum foil and air-dried.

3. The organic primary battery according to claim 2, characterized in that: The mass content of aromatic nitro compounds is above 30%.

4. The organic primary battery according to claim 1, characterized in that: The electrolyte is an alkali metal salt solution with a concentration of 0.5-5 mol / L.

5. The organic primary battery according to claim 4, characterized in that: The alkali metal salt is lithium perchlorate LiClO4, sodium perchlorate NaClO4, and potassium fluorosulfonyl imide KFSI. 6 . The organic primary battery according to claim 1 , wherein the battery is operated under acidic gas conditions; and the positive electrode active material is loaded on a carbon paper current collector.

Citation Information

Patent Citations

  • Lithium primary battery

    CN110556549A